2020
DOI: 10.7759/cureus.10771
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Bowing and Femoral Neck-Shaft Angle Evaluation Can Reduce Atypical Femoral Fractures in Osteoporotic Patients: A Scientific Report

Abstract: Bisphosphonates (BPs) are the mainstay of osteoporosis treatment due to their safety and efficacy. There is evidence that BPs medication may be complicated by atypical femoral fractures (AFFs). Prolonged administration of BPs is even more strongly associated with AFFs. AFF is a relatively rare complication of BPs when taking into account the huge population worldwide that benefits from this pharmacotherapy. AFF is, however, a serious complication of BPs treatment, which includes prolonged healing time and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The correlation between LB of the femur and BMD has been reported by several studies [1,12,22]. The present study showed a weak negative correlation between LB and trochanteric BMD, supporting the idea that the lower the femoral BMD the greater the LB.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The correlation between LB of the femur and BMD has been reported by several studies [1,12,22]. The present study showed a weak negative correlation between LB and trochanteric BMD, supporting the idea that the lower the femoral BMD the greater the LB.…”
Section: Discussionsupporting
confidence: 90%
“…Zyang et al reported that the extent of the bowing progresses with aging [11]. Papaioannou et al showed a correlation between femoral bowing and osteoporosis [12]. Other reports have suggested that the greater the anterolateral curvature, the more likely is the occurrence of an atypical femoral fracture (AFF) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation